Learner-generated contexts in the elementary EFL classroom: A GenAI-assisted framework - Tsai, Tun-Ju (Journal of English and Education (JEE), 2025)
Focus on the development of autonomous learning capacities among elementary English as a Foreign Language (EFL) learners highlights the need for systematic inquiry into effective pedagogical approaches. This paper proposes a conceptual framework to integrate Learner-Generated Contexts (LGC) and generative AI (GenAI) to bridge this gap by promoting self-directed learning within collaborative environments through structured scaffolding. Grounded in heutagogy and obuchenie models, the framework emphasizes student agency and socially constructed knowledge. Students, within the framework, co-create learning contexts, while GenAI provides adaptive scaffolding and content generation that align with digital literacy standards. The framework comprises four components: (1) Learner autonomy and agency, (2) Teacher-guided scaffolded learning, (3) Cultivation of a collaborative learning environment, and (4) Assessment and evaluation. The proposed framework could empower elementary EFL learners to navigate digital and collaborative contexts confidently; it may also serve as a guideline for elementary school instructors to promote student collaboration and learning autonomy through LGC-based approaches.